An Impact of Profitability Indicators of Standard Chartered Bank Nepal Limited (SCBL) - Sangraula, Prem Prasad (Damak Campus Journal, 2023)
This study has complemented in the field of study of the dissertation research results of the study indicated the “Impact of Earning Per Share, Return on Assets, Return on Equity, Net Profit Margin and Price Earnings Ratio on Market Value Per Share of Standard Chartered Bank Nepal Limited (SCBL)” and Standard Chartered Bank Nepal Limited (SCBL) in overall financial profitability position and its statement and financial events in the real service life of service provide bank. This dissertation research report work is different from other research work as this work is on effectiveness utilization and management of profit in the expansion of bank challenges on a particular sector. The main objective of this study is to analyze the trend, structure of Earning Per Share, Return on Assets, Return on Equity, Net Profit Margin and Price Earnings Ratio on Market Value Per Share significance relation through hypothesis and the study made over the period 2017/18 to 2021/22 taken as a sample year. The statistical methods of trend analysis and descriptive statistics like mean, standard deviation, coefficient of variation and hypothesis test were used to analyze the study outcomes.